2009
DOI: 10.1111/j.1095-8649.2009.02281.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Atlantic cod Gadus morhua in the Baltic Sea visit hypoxic water briefly but often

Abstract: Individual behaviour of Atlantic cod Gadus morhua in the presence of hypoxic water was measured in situ in the vertically stratified Bornholm Basin of the Baltic Sea. Considering all recaptured individuals, the use of hypoxic habitat was comparable to data derived by traditional survey data, but some G. morhua had migrated towards the centre of the c.100 m deep basin and spent about a third of their time at oxygen saturation <50%, possibly to forage on zoobenthos. Maximal residence time per visit in such hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 15 publications
2
59
0
Order By: Relevance
“…Obviously this is related to increase of intensity of baroclinic (or summer) infl ows . The exceptional baroclinic infl ows were reported in summer/autumn , 2006, and 2009-2010(Nausch et al 2014). Due to this in the eastern Baltic spawning grounds in the recent years there is an increase of salinity and decrease of oxygen saturation in the intermediate water layers that allows the formation of small suitable reproduction volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously this is related to increase of intensity of baroclinic (or summer) infl ows . The exceptional baroclinic infl ows were reported in summer/autumn , 2006, and 2009-2010(Nausch et al 2014). Due to this in the eastern Baltic spawning grounds in the recent years there is an increase of salinity and decrease of oxygen saturation in the intermediate water layers that allows the formation of small suitable reproduction volume.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the environment where spawning of cod takes place does not always correspond to the conditions necessary for egg survival. Spawning cod has been observed at salinity of 9.5‰ and oxygen 1.5 mL· L -1 (Plikš and Kalejs 1990, Neuenfeldt et al 2009, Schaber et al 2011). In such situation cod eggs have low probability to survive.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, at any given routine swimming speed, the avoidance P O2 threshold of anaemic fish was consistently higher than that of normocythaemic fish. A number of studies have observed fish entering potentially dangerous levels of hypoxia on a voluntary basis (Jones, 1952;Höglund, 1961;Herbert et al, 2011;Claireaux et al, 1995;Kaartvedt et al, 2009;Neuenfeldt et al, 2009;Wannamaker and Rice, 2000) implying that residence time under low levels of oxygen is a key driver of avoidance. Recently, Herbert and colleagues have shown that cod (G. morhua) voluntarily swim into critical P O2 without any change in their behaviour but only when they have access to an O 2 refuge (Herbert et al, 2011).…”
Section: Discussion Effects Of Anaemia On Aerobic Physiology and Avoimentioning
confidence: 99%
“…When hypoxia is spatially limited and fish have the option to move between different areas, complete low-O 2 avoidance would naturally represent an adaptive response as a result of its immediate benefit to basic aerobic functions at moderate P O2 and survival at extremely low P O2 . However, and perhaps surprisingly, numerous studies have identified that fish enter severe hypoxia voluntarily (Jones, 1952;Höglund, 1961;Claireaux et al, 1995;Wannamaker and Rice, 2000;Kaartvedt et al, 2009;Neuenfeldt et al, 2009;Herbert et al, 2011). With some evidence of larger predatory species being less hypoxia tolerant than smaller prey species, deliberate excursions into hypoxic water have proven beneficial to some fish as a form of predator avoidance (Robb and Abrahams, 2003;Kaartvedt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation